The Labour Market Effects of a Refugee Wave. A Replication Study of Peri and Yasenov (Journal of Human Resources, 2019) - Michael Christl (International Journal for Re-Views in Empirical Economics (IREE), 2020)
Peri and Yasenov (2019) exploit a natural experiment, the Mariel boatlift of 1980, to analyse the impact of immigration on wages and other labour market outcomes of natives. The authors find no impact of this (immigrant) labour supply shock on the wages of local workers. These results are heavily discussed in the literature, making it a good example for replication to check the robustness of the findings. This paper analyses the impact of the selection of control variables when choosing the synthetic control group and the influence of the sample choice on the findings of the original study. The replication exercise shows that the original results are very stable to several robustness checks. Even though restricting the analysis to a smaller sample influences the results slightly, there is still no evidence of a significant (negative) impact of the labour supply shock on wages of locals.
http://dx.doi.org/10.15456/iree.2020136.181539
Keywords: J3; J61; 330; Immigration; Wages; Mariel boatlift; Synthetic control method; Measurement error; Replication study